2010
DOI: 10.1155/2010/432306
|View full text |Cite
|
Sign up to set email alerts
|

Will Universal Access to Antiretroviral Therapy Ever be Possible? The Health Care Worker Challenge

Abstract: The United Nations millennium development goal of providing universal access to antiretroviral therapy (ART) for patients living with HIV/AIDS by 2010 is unachievable. Currently, four million people are receiving ART, of an estimated 13.7 million who need it. A major challenge to achieving this goal is the shortage of health care workers in low-income and low-resource areas of the world. Sub-Saharan African countries have 68% of the world's burden of illness from AIDS, yet have only 3% of health care workers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Given observed and projected economic limitations to achieving adequate health professional staffing exacerbated by the AIDS epidemic, 35,36 the LHWs provide an approach to help address the health worker gap in poor, rural settings. 37 Although not a replacement for nurses and other professionals, we found that LHWs extended the reach of clinic professional staff and were a relatively rapid and economical solution to staffing shortages. Since LHWs are local staff, they do not require housing at the remote, rural health facilities.…”
Section: Discussionmentioning
confidence: 79%
“…Given observed and projected economic limitations to achieving adequate health professional staffing exacerbated by the AIDS epidemic, 35,36 the LHWs provide an approach to help address the health worker gap in poor, rural settings. 37 Although not a replacement for nurses and other professionals, we found that LHWs extended the reach of clinic professional staff and were a relatively rapid and economical solution to staffing shortages. Since LHWs are local staff, they do not require housing at the remote, rural health facilities.…”
Section: Discussionmentioning
confidence: 79%
“…5,7 There is a severe shortage of professional health workers in sub-Saharan African countries. [8][9][10][11] As a response to this, the number of lay health workers in ART programs has been substantially increased during the last half-decade, 12, 13 and there have been calls to further strengthen community-based adherence support (CBAS) initiatives for patients receiving ART. 14,15 To justify further resource allocation to such interventions, evidence of their effectiveness is required.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa carries 68% of the world’s HIV/AIDS burden but has only 3% of healthcare workers worldwide and 1% of financial resources for health. 16,17 Surgical disparities are even more profound, and Rwanda is no exception, with less than 0.5 total surgeons per 100 000 persons. 15 Given the scarcity of surgical personnel in Rwanda, healthcare worker safety should be a priority.…”
Section: Discussionmentioning
confidence: 99%